2020
DOI: 10.21829/azm.2020.3612164
|View full text |Cite
|
Sign up to set email alerts
|

Diversidad y conservación de anfibios y reptiles en un área protegida privada de una región altamente transformada en el sur de Veracruz, México

Abstract: 2020) Diversidad y conservación de anfibios y reptiles en un área protegida privada de una región altamente transformada en el sur de Veracruz, México. Acta Zoológica Mexicana (nueva serie), 36, 1-14. https://doi.org/10.21829/azm.2020.3612164 RESUMEN. El establecimiento de Áreas Protegidas Privadas (APPs) es una de las estrategias para la protección de la biodiversidad ante la modificación del hábitat en bosques tropicales; sin embargo, su importancia en conservación ha sido poco evaluada. En este trabajo esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
1
4
0
2
Order By: Relevance
“…Also, in this work, the authors found a strong association between beta diversity and the climate and soil moisture categories rather than physiographic categories [34]. The same results were obtained at the local level among the amphibians from three NPAs in the state of Veracruz, with a total beta diversity ranging from 60 and 100% [35,36]. In two pairs, turnover was more important than the differences in richness, and the opposite occurred in one pair [35].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Also, in this work, the authors found a strong association between beta diversity and the climate and soil moisture categories rather than physiographic categories [34]. The same results were obtained at the local level among the amphibians from three NPAs in the state of Veracruz, with a total beta diversity ranging from 60 and 100% [35,36]. In two pairs, turnover was more important than the differences in richness, and the opposite occurred in one pair [35].…”
Section: Discussionsupporting
confidence: 69%
“…In comparison to caudates, anurans were distributed more broadly, in as many as 10 subprovinces (X = 2.87 subprovinces), and the caudates were distributed in as many as three subprovinces (X = 1.3 subprovinces, Table 2). Notably, the SMO had 88 species (62 anurans and 26 caudates), with 70.45% endemism (62 species: 36 anurans and 26 caudates), while, nationally, there was 21.6% endemism (19 species) at the national level (17 anurans and 2 caudates) and 49% endemism (43) at the state level (19 anurans and 24 caudates), of which 86.7% (36) are endemic to this subprovince (16 anurans and 20 caudates). There is a relationship between the subprovince area and amphibians' richness; this relationship is also observed in anurans and caudates separately (r 2 = 0.461 p < 0.017; r 2 = 0.407 p < 0.025; and r 2 = 0.51 p < 0.0137, respectively).…”
Section: Species Richness and Endemismmentioning
confidence: 99%
“…However, the presence of C. angustatus in human-modified tropical landscapes, such as where we recorded individuals, suggests that some anthropogenic matrices may be suitable for this species. Additionally, this species has been reported in floodplains and semi-permanent water bodies surrounded by cattle pastures (Reynoso et al 2016), in pastures (Aguilar-López et al 2020), or in sugarcane fields (Vásquez-Cruz and Reynoso-Martínez 2020). This is not surprising, as some aquatic turtles can inhabit several aquatic environments (e.g., rivulets or temporary ponds) located inside anthropic matrices, such as tree plantations and cattle pastures (Legler and Vogt 2013;Petrozzi et al 2021).…”
Section: Discussionmentioning
confidence: 97%
“…Con este estudio la fauna de reptiles para el municipio de Santiago Nonualco representa el 35% de los reptiles reportados para El Salvador (103 especies). La riqueza de especies registrada es alta al compararla con otros estudios en la región mesoamericana donde se han muestreado áreas más extensas, hábitats mejores conservados y lapsos más largos (Guerra-Centeno et al, 2014;Aguilar-López et al, 2020;Nahuat-Cervera et al, 2020).…”
Section: Discussionunclassified